International Conferences Internet Technologies &Amp; Society 2019 and Sustainability, Technology and Education 2019 2019
DOI: 10.33965/ste2019_201901l010
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Water Hyacinth (Eichhornia Crassipes) to Vermicompost Through Application of the Vermicomposting Technology

Abstract: This study focuses on the microbial degradation of water hyacinth (Eichhornia crassipes) to vermicompost as a bioconversion strategy. Water hyacinth was vermicomposted using Eisenia Fetida earthworms loaded at a rate of 150 earthworms/L over a period of 35 days. The changes in water hyacinth total organic carbon (TOC), chemical oxygen demand (COD), total nitrogen (TP), and total phosphorous (TP) and total potassium (TP) were measured using standard methods. Linear models were generated using MATLab 13.0 to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similar to this is SolarAid in African countries, which aims to eradicate the use of kerosene lamps by providing affordable solar lights to off-grid communities (Zarsky & Wilson, 2009). Adding to the list, frugal innovations such as bottle lights in the Philippines (Kuo, 2014), the Wonderbag and Reel Gardening in Africa (Manyuchi et al, 2019;Mawire et al, 2020;Nieuwenhuizen, 2020) and the Hand Talk in Brazil are some classic examples of frugal technologies in the world. 'Any technology that claims the mantle of "appropriate" should also be adaptable and flexible, while eliminating-or at least minimising-adverse environmental impacts' (Darrow & Saxenian, 1986).…”
Section: India's Technological Transformation and Its Changing Global...mentioning
confidence: 99%
“…Similar to this is SolarAid in African countries, which aims to eradicate the use of kerosene lamps by providing affordable solar lights to off-grid communities (Zarsky & Wilson, 2009). Adding to the list, frugal innovations such as bottle lights in the Philippines (Kuo, 2014), the Wonderbag and Reel Gardening in Africa (Manyuchi et al, 2019;Mawire et al, 2020;Nieuwenhuizen, 2020) and the Hand Talk in Brazil are some classic examples of frugal technologies in the world. 'Any technology that claims the mantle of "appropriate" should also be adaptable and flexible, while eliminating-or at least minimising-adverse environmental impacts' (Darrow & Saxenian, 1986).…”
Section: India's Technological Transformation and Its Changing Global...mentioning
confidence: 99%
“…Due to its capacity to take up heavy metals and grow in contaminated water, it has been utilized as a phytoremediation agent for wastewater treatments [20]. It has also been investigated as a possible source of bioenergy and fertilizers [21,22]. The plants have historically been used to treat digestive issues like atulence, intestinal worms, diarrhoea, and atulence.…”
Section: Introductionmentioning
confidence: 99%
“…Jain and Sheth [8] calculated a power execution check for a biomass cooking stove and originated with formulation acceptance and consequently upgrading of runtime to almost 85 minutes which is around 30% overall enhancement. Manyuchi et al [9] worked on enhancement of efficiency for conventional stove, they found that by changing some parameters on design point of view for conventional stove, energy effectiveness and energy storage enhancement takes place, which is a best method. Prasanna kumaran et al [10] designed merging of cooking plates in Favor of recovery of discarded hotness in the energy proficient wooden stove, where it is established that such acceptance guided with perfection in effectiveness together with reduction in contamination levels.…”
Section: Introductionmentioning
confidence: 99%